Literatur review : hubungan eosinofil pada kejadian asma akut - Fatmawati; Fatmaria; Parhusip, Mual Bobby Enrico (Fakultas Kedokteran Universitas Palangka Raya, 2023)
An increase in the number of eosinophils in the airways is a pathological feature of asthma. Airway eosinophils are frequently associated with poor lung function measurements. This study is a literature review type which aims to find out whether there is a relationship between eosinophils in the incidence of acute asthma. The method in this study uses a Systematic Literature Review. Source of data obtained from research journals. The journals obtained were 9 national journals and 6 international journals. The results obtained were 9 journals (60%) which agreed that there was a relationship between eosinophils in the incidence of acute asthma. Whereas 6 (40%) journals said it was not related, one of the factors that could occur was because the patient arrived late so that when the eosinophil examination in the blood decreased and infiltration into the tissues had occurred, besides that it was also considered the presence of comorbidities in asthma sufferers.